Design and simulation algorithm for cam system analysis (2004)
Computational algorithm and various computer aided methods are now routinely being used in the design of numerous kinds of engineering systems, sybsystems and components. In particular some of these computational methods perform dynamic and kinematic analysis of mechanisms. In this work an algorithm for the design and profile simulation of plate cam with flat-face followes using standard cam motions has been developed. The developed algorithm computers the two critical design output parameters among others namely; the prime circle radius and follewer face width, and finally generates the cam coordinates for the cam profile being designed. The design algorithm developed in this work makes the design of cam systems less tedious, thereby, making various extensive studies o the comparative design analysis of such systems possible.